Narrating for taking perspectives and regulating emotions: The role of scaffolding and repetition on interpersonal anger narratives of children with adverse childhood experiences - Eleonora Bartoli; Tilmann Habermas (Acta Psychologica)
Background: The interplay between narrative abilities, emotion regulation, and perspective taking is critical, particularly for children with Adverse Childhood Experiences (ACE). However, this relationship remains underexplored in the context of ACE. Objective: This study aimed to examine how different narrative modalities affect emotion regulation and perspective taking in children with ACE when recounting everyday anger events. Additionally, it explored whether a scaffolding interview could enhance these outcomes compared to simple narration. The hypotheses were: (1) narration improves emotion regulation and perspective taking; (2) scaffolding is more beneficial than narration alone; (3) narration boosts positive emotionality and reduce negative emotionality for anger events; (4) these effects on emotionality differ for different narrative conditions. Participants and setting: The study involved 33 Italian-speaking children aged 6 to 14 from residential childcare communities in Italy (57.6 % female). Methods: Data on sociodemographic factors, ACE exposure, and trauma symptoms were gathered through informant-report questionnaires. Children narrated three interpersonal anger events under different conditions (Repetition, Scaffolding, and Non-Repeated) across two sessions a week apart. They rated each event's emotionality before and after each session. Narratives were analyzed for indicators of emotion regulation and perspective taking. Results: Narration did not improve emotion regulation or perspective taking, nor was scaffolding more effective. Only negative emotionality decreased over time, with no significant differences between the narrative conditions. Conclusions: The lack of significant findings may be due to the low severity of the events narrated and the limited effectiveness of the scaffolding provided.